Analysis of the Influence of Interest Rates on Cash Flow in Real Estate Investment Funds - Santi, Lidwina Maura; Gilba, Nasya Safina (Operations Research: International Conference Series, 2025)
Interest rates play a significant role in determining financing costs, property values, and rental income, all of which have a direct impact on net cash flows derived from property investments. When interest rates rise, borrowing costs increase, reducing the net cash flow available for distribution to REIT unitholders. Conversely, a decrease in interest rates can increase net cash flow due to lower financing costs. This study aims to analyze the effect of interest rates on cash flow in Real Estate Investment Trusts (REITs) using sensitivity simulation methods, modified duration, and risk measurement using Value at Risk (VaR). The results show that changes in interest rates have a significant impact on REIT cash flow, with an increase in interest rates worsening profitability and a decrease in interest rates having a positive impact. The effect of interest rates shows that REIT investors and managers need to pay attention to dynamics in strategic planning to minimize financial risk and maximize profits.